Cooperation and Competition in the Context of Organic and Mechanic Worldviews – A Theoretical and Case based Discussion - Ims, Knut J. (Journal of business ethics, 2006)
In this study we argue that there is an interconnection between; the mechanistic worldview and competition, and the organic worldview and cooperation. To illustrate our main thesis we introduce two cases; first, Max Havelaar, a paradigmatic case of how business might function in an economy based upon solidarity and sustainability. Second, TINE, a Norwegian grocery corporation engaged in collusion in order to force a small competitor out of the market. On the one hand, in order to encourage market behaviour that integrates economic, societal and environmental values we find that transparent cooperation within a context of an organic worldview takes care of important intrinsic as well as instrumental values. On the other hand, we find evidence for asserting that cooperation based upon a mechanistic worldview, typically leads to group egotistical consequences undermining the long term common good.